Potential Analysis of Sea Wind Energy To Electricity at Ancol Beach Jakarta - Kunto Wibowo (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The background of this research is how to find out the energy level on the Jakarta coast that utilizes sea wind energy into electrical energy with the presence of wind energy as a source of electrical energy in the future at Ancol Beach will be able to help the surrounding community and especially Ancol Beach in developing new and environmentally friendly energy sources. so that it can be developed into energy that can illuminate or help Ancol Beach in creating energy that can always exist. The method used in this research is to use literature reviews and conduct tests on Ancol Beach so that Ancol Beach can know the level of sea wind energy that can be converted into electrical energy. The problem raised in this study is how to change wind energy on a beach so that it can be utilized into good and environmentally friendly electrical energy. The purpose of this study is how to find out the results of the wind power of Ancol Beach Jakarta which will be converted into electrical energy because by knowing how strong the wind strength of Ancol Beach Jakarta will be, you will be able to find out how much power that will be generated can be converted into electrical energy.